2020
DOI: 10.48550/arxiv.2005.14555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spectral evolution of X-ray pulsar 4U 1901+03 during the 2019 outburst based on Insight-HXMT and NuSTAR observations

Armin Nabizadeh,
Sergey S. Tsygankov,
Long Ji
et al.

Abstract: We report on detailed spectral analysis of emission from X-ray pulsar 4U 1901+03 using the data obtained by the Insight-HXMT and NuSTAR observatories during the 2019 outburst of the source. Thanks to the extensive coverage of the outburst by Insight-HXMT, we were able to investigate spectral evolution of the source as a function of flux, and compare these results to the previous reports with focus on the properties of a putative absorption feature at around 10 keV. In particular, we demonstrate that the broadb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…As observed by Nabizadeh et al (2020) and Coley et al (2019) when Obs3 and Obs4+Swift spectra were fitted some negative residuals were observed near 30 keV and fitting the spectra with absorption model we estimated the line energy about 30.37 and 30.23 keV for these observations respectively and were consistent with the value estimated by the authors. However, no negative residuals near 30 keV were observed in the first two NuSTAR spectra which were having higher flux compared to the last two observations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…As observed by Nabizadeh et al (2020) and Coley et al (2019) when Obs3 and Obs4+Swift spectra were fitted some negative residuals were observed near 30 keV and fitting the spectra with absorption model we estimated the line energy about 30.37 and 30.23 keV for these observations respectively and were consistent with the value estimated by the authors. However, no negative residuals near 30 keV were observed in the first two NuSTAR spectra which were having higher flux compared to the last two observations.…”
Section: Discussionsupporting
confidence: 91%
“…In NuSTAR spectra weak residuals are observed around 10 keV due to tungsten L-edge of the NuSTAR optics (Madsen et al 2015;Fürst et al 2013). The 10 keV feature in other pulsars were present in the spectra of different instruments of different satellites (Coburn et al (2002)) like in the case of 4U 1901+03 where this feature was observed by RXTE (Reig & Milonaki 2016) and Insight -HMXT (Nabizadeh et al 2020), thus clearing doubt about the instrumental origin of the feature. We have also seen that the feature is present even if we used another continuum model COMPTT instead of CUTOFFPL.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations